KEARIFAN LOKAL WAYANG KULIT BALI SEBAGAI MEDIA TUNTUNAN DAN TONTONAN PADA ERA DIGITAL - I Gede Sutana; I Kadek Edi Palguna (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
The world of puppets, known as noble arts, is a characteristic of the cultural identity of the Indonesian people that spreads in every region. Particularly in Bali, the existence of shadow puppet art has become the identity of local wisdom as well as in its role as offering to God, which is implemented in religious ritual practices of the Balinese people, on the another side, has a function as a dish in the form of spectacle and guidance. The Balinese shadow puppet show has always been in high demand, until now in the onslaught of the current modernization of the dynamics of the Balinese shadow puppets are able to keep abreast of the times. This is reflected in the YouTube as a modern media product that is used by the public both to get entertainment or something else, including a life guidance. Recently on YouTube, a new innovation idea emerged in the packaging of the Balinese shadow puppet show made by a puppeteer who is already familiar in the Balinese shadow puppet show, namely